2020
DOI: 10.36660/abc.20190404
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas Depressivos estão Associados a Níveis Séricos Elevados de Colesterol de Lipoproteína de Baixa Densidade em Idosos com Diabetes Mellitus Tipo 2

Abstract: Background: Type 2 Diabetes Mellitus (T2DM) is common in older adults, who also present a high level of risk factors for cardiovascular disease (CVD), such as dyslipidemia. However, the role of depression in T2DM patients and its relationship with CVD risk factors are understudied. Objective: The present study aimed to investigate the relationship between depressive symptoms (DS) and known cardiovascular risk factors in community dwelling older adults with T2DM. Methods: This is a cross sectional study, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
1
2
0
5
Order By: Relevance
“…The presence of dyslipidemia was associated with higher means of depressive symptoms, corroborating the data of a study carried out in Recife -PE, which identified that changes in the lipid profile with increased levels of LDL-C, HDL-C and systolic blood pressure were related to a higher number of depressive symptoms in aged diabetics 22 .…”
Section: Discussionsupporting
confidence: 86%
“…The presence of dyslipidemia was associated with higher means of depressive symptoms, corroborating the data of a study carried out in Recife -PE, which identified that changes in the lipid profile with increased levels of LDL-C, HDL-C and systolic blood pressure were related to a higher number of depressive symptoms in aged diabetics 22 .…”
Section: Discussionsupporting
confidence: 86%
“…É importante ressaltar que nosso estudo identificou os fatores de risco e protetores em portadores de doenças crônicas, incluindo as cardiovasculares, pulmonares e diabetes. Acreditamos também que essas três enfermidades prévias permitam maior suporte e apoio quando comparadas às outras doenças crônicas, uma vez que suas fisiopatologias, formas clínicas, métodos de tratamento e possibilidade de acompanhamento são mais difundidos na sociedade, com amplo tratamento no Sistema Único de Saúde do Brasil (Fittipaldi et al, 2020), o que predispõe menores índices de transtornos psíquicos. Infelizmente, poucos estudos abordam especificamente o grupo de pacientes com doenças crônicas e sua associação aos transtornos mentais (Zhang et al, 2016).…”
Section: Resultsunclassified
“…A presença de dislipidemia esteve associada a maiores médias de sintomas depressivos, o que corrobora os dados de um estudo realizado em Recife -PE, o qual identificou que alterações no perfil lipídico com aumento nos níveis de LDL-C, HDL-C e pressão arterial sistólica estavam relacionados a um maior número de sintomas depressivos em idosos diabéticos 22 .…”
Section: Discussionunclassified
“…A associação entre as variáveis complicações do diabetes e retinopatia apresentou significância estatística com a sintomatologia depressiva, sendo evidenciado que os idosos com complicações da doença, principalmente, a retinopatia, exibiram maiores médias de sintomas depressivos. As complicações relacionadas ao diabetes comprometem a qualidade de vida da pessoa idosa e potencializam as vulnerabilidades relacionadas à doença e ao envelhecimento, o que favorece o surgimento de problemas psíquicos 22 .…”
Section: Discussionunclassified